Increased Millennial Participation Through Utilization of Information Technology for Tourism Village Creative Economy Development (Study Case Cikaso Village Kuningan Regency West Java) - Mukhamad Kholil Aswan Aswan; Henry Yuliamir; Enik Rahayu (Institute of Computer Science (IOCS), 2021)
This study was conducted to determine the increase in millennial participation through the use of information technology for the development of the creative economy of the Cikaso tourism village, Kuningan District, West Java. This research data uses qualitative descriptive research with a SWOT (strength, weakness, opportunity, and threat) approach. Descriptive research is research that describes the condition of an object without a hypothesiss. The author then concludes that the data obtained from the SWOT method analysis is then combined with STP analysis (segmenting, targeting, positioning) to find technology for the development of the creative economy with the right technology.